THE EFFECTIVENESS OF BIBLIOTHERAPY IN IMPROVING HONEST CHARACTER ON THE ELEMENTARY STUDENTS - Anggi Citra Apriliana; Titi Setiawati (Widyagogik, 2020)
The purpose of this study is to find out the effectiveness of bibliotherapy in improving honest character of elementary school students. The background in this research is the low honest character of elementary school students. Based on the results of interview to teachers and parents, the character that must be strengthened on the elementary students are honest character. This is because many students in elementary school started to act dishonestly from cheating and lying. Bibliotherapy is a method of healing (therapy) using books.  The type of this research is a pre-eksperimental design with one group pretest-posttest design. The subjects are 10 students from 3rd grade of SDN Kananga in Jatinangor district-Sumedang Regency. The research data were collected through the pretest and posttest scores using the measurements of the honestly scale. Based on the calculation results of the N-Gain score test, it shows that the average N-Gain score using bibliotheraphy is 78.76 with a minimum N-Gain score is 74.15 and a maximum N-Gain score is 83,36. It is included in the effective category with high level of effectiveness criteria. So it can be concluded that bibliotherapy can improve the honest character of elementary students in SDN Kananga.